Bilateral Bochdalek Hernias Associated with Arnold-Chiari I Malformation - Julian Fazi; Visad Patel; Cara Bryan (Case Reports in Radiology)
A Bochdalek hernia is a posterolateral diaphragmatic defect that is either congenital or acquired. The contents of the hernia range from fat to intra-abdominal organs. They are primarily pathologies of neonates and most commonly occur unilaterally. These hernias have been described in isolation and as one part of a group of malformations. There have been reports of Bochdalek hernias in association with myelomeningocele and other neural tube defects. We present a unique case of bilateral Bochdalek hernias in a 35-year-old female with an Arnold-Chiari I malformation.